Origin of implication: how do innocent individuals enter the criminal justice system? - Lowrey-Kinberg, Belén (Crime & delinquency, 2019)
Drawing from the investigative policing literature, we develop a typology for how innocent defendants become suspects in criminal investigations. We use the Preventing Wrongful Convictions Project (PWCP) dataset and multivariate modeling to examine the case and defendant characteristics that predict how an innocent defendant became a suspect. We found that investigators identify suspects in eight primary ways. The most common in the PWCP dataset were victim/eyewitness identification, citizen identification, and intentional misidentification. Defendant’s race, age, criminal history, relationship to the victim, cognitive/mental status, and whether the victim survived were strongly associated with an innocent defendant’s origin of implication. These results illuminate how tunnel vision begins in cases with innocent defendants, and how police practices may prevent innocent individuals from becoming suspects.